Caring in Cancer Patient during Covid-19 Pandemic: A literature review - Huda, Nurul (Universitas Pendidikan Indonesia, 2020)
ABSTRACT During this Coronavirus disease-19 (Covid -19) Pandemic, the challenges for appropriate and safe delivery nursing care is becoming main concerns since cancer patients are at high risk to be infected. Oncology nurse must reassure that the patients still get the optimal treatment while in other part they have to keep their patients safe. However, the change of provision of care in order to protect cancer patients must pay more attention. The aim of this paper was to review the literature on both the impact of Covid 19 to the provision of cancer care and nursing workforce. The implications of these findings for cancer patients will also be discussed. The electronic Science direct, Googlescholar and Pubmed databases were used to identify relevant articles. A combination of keywords: cancer, care, Corona virus 19, Covid-19 and Pandemic were used to identify relevant articles. Ten articles were included in the review. The broad issues were the impact of Covid 19 on nursing delivery care and the impact to the workforce. In terms of cancer care delivery, the Oncology teams are adopting new ways to minimise the risk of Covid 19 to the patients and their staff while at the similar times they have to reassure that the patients get the optimum care. Triage patients, adjusting treatment and limitation of visitor’s access to the patients is kind of changes that could do. A serious shortage and the availability of personal protective equipment are the major concern in nursing workforce changes during this pandemic. Planning or resuming cancer treatment and screening to mitigate the risk is the most important way to get the best outcomes. Hence, nurse has been pushed to adapt quickly and give their optimum nursing care to patients as well as protect themselves from cross infection ABSTRAKSelama masa pandemi Coronavirus 19, tantangan terhadap pemberian asuhan keperawatan pada pasien kanker menjadi perhatian utama. Hal ini dikarenakan, pasien kanker adalah pasien dengan resiko tinggi tertular infeksi. Perawat oncology harus memastikan bahwa pasien yang mereka rawat tetap mendapatkan perawatan yang optimal walaupun disisi lain mereka harus menjaga keamanan pasien. Oleh karena itu perubahan cara layanan dalam rangka melindungi pasien harus menjadi fokus tersendiri. Tujuan dari artikel ini adalah melakukan literature review tentang impact Covid 19 terhadap layanan pasien kanker dan lingkungan kerja di unit kerja keperawatan. Aplikasi dari temuan juga didiskusikan di artikel ini. Electronic data base seperti Science Direct, Googlescholar dan Pubmed digunakan untuk mencari artikel yang berhubungan. Kombinasi dari kata kuci : cancer, care, Corona virus 19, Covid-19 and Pandemic digunakan untuk telusur artikel. 10 artikel terseleksi. Isu utama yang didapatkan adalah efek dari Covid 19 terhadap cara pemberian asuhan keperawatan dan perubahan yang terjadi dalam lingkungan tenaga kerja. Dalam hal pemberian asuhan keperawatan diketahui bahwa team oncology mengadopsi cara baru untuk mencegah penyebaran Covid-19 kepada pasien dan staff dengan melakukan triage, menunda atau menyesuaikan treatment dan membatasi akses pengunjung ke pasien. Kekurangan tenaga kerja dan ketersediaan alat pelindung diri menjadi issue utama dalam ketenagakerjaan di area keperawatan selama masa pandemi. Merencanakan atau meresume kembali asuhan yang diberikan dan melakukan screening untuk mitigasi resiko infeksi merupakan salah satu cara yang paling naik untuk pelayanan yang terbaik. Oleh karena itu perawat harus bisa beradatasi secara cepat terhadap perubahan dan memberikan pelayanan keperawatan yang optimum dengan tidak melupakan perlindungan diri terhadap diri mereka sendiri dari infeksi silang.